Effects of noises on near infrared sensor for blood glucose level measurement - Kiki Prawiroredjo; Engelin Shintadewi Julian (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper proposed the method of measuring glucose level in solution using near infrared light (NIR) and photodiode sensor. We studied noises that occurred on the output signal of NIR sensor in three different room conditions in order to know the effects on this sensor output voltage stability. The sensor’s circuit consisted of a 1450 nm NIR light emitting diode, a photodiode as the receiver, transimpedance amplifier, a notch filter, and a 4th order low pass filter. The results indicated that sunlight passing through windows was the most influencing factor caused the unstable sensor output voltage. Filters removed the effective voltages and the average sensor output voltages from the three rooms were 4.6825 V for air media, 2.2809 V for water media and 2.3368 V for glucose solution media. The output voltages tended to increase for one-hour measurement about 10 to 40 mV for air media, 40 to 90 mV for water media and 30 to 80 mV for glucose solution media. This sensor could only be used in a short time and suitable in a room without sunlight. Based on the voltage difference of the average sensor output voltage with water and glucose solution media, the sensor had the potential to be a blood glucose level meter.